Improving the Students’ Motivation in Learning Vocabulary Using Song Lyrics - Setiana Sri Wahyuni Sitepu; Eka Safitri; Nur Najibah Sukmawati; Sukma Septian Nasution; Laksmy Ady Kusumoriny (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This study aims to increase the students' motivation in learning vocabulary using song lyrics in the seventh grade of SMP Citra Bangsa. This classroom action research uses tests, observations, questionnaires, and documentation to determine the improvement that occurs in each cycle. Tests given to Pre-Test, Post-Test cycle 1, and Post-Test cycle 2 showed that the average score of each vocabulary test in the class increased significantly. In the Pre-Test, the mean score was 41.25. Then in the Post-Test cycle 1 the average score raised to 56. In the Post-Test cycle 2, the average score reached 63.5. The improvements proved that song lyrics is worth implementing in teaching vocabulary. It is supported by the results of observations which showed an increase in terms of students' motivation in learning vocabulary. The results of the questionnaire also showed an increase in the number of positive questions. While the number of negative questions decreased. Thus, it can be concluded that there is a significant increase in motivation and vocabulary achievement of seventh grade students of SMP Citra Bangsa after they are taught to use song lyrics.